Open Source Augmented Reality in Data Center Infrastructure Maintenance - Barth, Vitor; Vogel, Adriano; Griebler, Dalvan; Pinho, Marcio Sarroglia (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
The use of Augmented Reality (AR) is increasing in several application domains. However, applying AR in data center infrastructure management is still limited. Although solutions are providing DCIM (Data Center Infrastructure Management) with augmented reality, they are paid commercial applications that do not provide the source code. Therefore, using such solutions, their reproducibility, and their evaluation is difficult in academic and computational research environments. In this vein, this work aims to create a prototype of an open-source AR mobile application for maintenance management in data centers. Moreover, this work provides a theoretical foundation based on a literature review of solutions available in the academic and industry fields. We evaluated the proposed solution with qualitative and quantitative methods, including user feedback on the developed application and comparison to OpenDCIM - a well-known tool for data center management. The results from the qualitative evaluation demonstrate that the proposed solution improves the user experience. However, it is not possible to infer significant productivity gains from the quantitative evaluation.